Formulation, Integration, and Impact of Vision and Mission in Hospital Strategic Management a Systematic Review - Jodii Arlan Kurnia; Diah Prawesti; Aryo Dewanto (Yayasan Darussalam Bengkulu, 2026)
Background: In the face of increasingly complex healthcare systems, vision and mission statements play a crucial role in hospital strategic management. However, their formulation and integration often remain underutilized, leading to gaps between organizational goals and actual performance. Method: A systematic review was conducted following the PRISMA 2020 guidelines. A total of 15 peer-reviewed articles published between 2010 and 2024 were analyzed to explore patterns, strategies, and outcomes related to vision–mission formulation and integration in hospital management. Results: Findings show that participatory formulation of vision and mission fosters organizational ownership and commitment. Strong integration into managerial systems enhances strategic effectiveness, inter-unit coordination, and overall hospital governance. A well-internalized vision–mission is associated with enhanced operational efficiency, employee engagement, and patient satisfaction. Conversely, insufficient stakeholder involvement and weak internalization may cause organizational disorientation and performance decline. Conclusion: The study underscores the importance of strengthening the continuous cycle of formulation, integration, and evaluation of vision and mission statements. This process serves as a strategic foundation for building adaptive, quality-oriented, and sustainable hospital transformation.